Study on Application Effect of Sand Consolidating Agent for the Slope of Highway Subgrade in Season Frozen Zone - Dongliang Zhang; Guangqing Yang; Xiaodi Niu; Lu Zhang; Zhijie Wang (Advances in Civil Engineering)
In deep season frozen areas, the solidified layer is easy to be destroyed due to the influence of freeze-thaw cycles after the surface layer of the sandy slope is solidified by chemical methods. In order to study the application effect of the new sand consolidating agent after solidifying sand body, the mechanism of strength formation was analyzed by scanning electron microscopy (SEM). The freeze-thaw cycle tests were carried out on sand consolidating samples. The direct shear tests and unconfined compressive strength tests were carried out before and after freeze-thaw cycles to analyze the freeze-thaw resistance of sand consolidating samples. The sand consolidation agent was tested on-site, and its strength was tested to observe its effect. The results showed that the adhesive membranes on the surface of sand particles were formed by the sand consolidating agent, which increased the cohesion and strength of sand particles. After freeze-thaw cycle tests, the cohesion, internal friction angle, and compressive strength of the solidified sand gradually decreased with increasing freeze-thaw cycles. The decreasing rate reduced from fast to slow and then tends to be stable. The failure mode of samples changed from brittle failure to plastic failure. The sand consolidating layer can effectively prevent collapse of the sandy slope. Combining with the external-soil spray seeding, the sand consolidation layer is beneficial to the growth of plants.